Output Variability under Monetary Policy and Exchange Rate Rules - Weber, Warren E. (Journal of Political Economy, 1981)
This paper examines the controversy concerning the relative desirability of fixed versus flexible exchange rates by examining whether a country can achieve a smaller variance of domestic output around its full employment path operating under an exchange rate rule or under a money supply rule. The paper finds that neither policy will always dominate the other. However, it does find that if shocks in one market of the economy are large relative to shocks to other markets, then one type of rule can be shown to dominate the other.